The Prophetic Character of Christian-Oriented Sexual Freedom in the Conjugal Relationship in the Thinking of Moral Theologians - Szaniszló, Inocent-Mária Vladimír (Verbum Vitae, 2023)
In 2023, people on the European continent find themselves recovering after several social upheavals caused by the COVID-19 pandemic, as well as several military conflicts, especially the war in Ukraine. At the same time, however, there is a significant wave of migration to the so-called safe (socially secure) countries of Western Europe. Despite the significant problems that this migration causes for a politically polarized Europe, Western European, but also other countries are experiencing an astoundingly strong demand for labor (e.g. Germany openly talks about the economic need for up to 400,000 jobs per year). This year marks the 55th anniversary of the publication of the long-awaited encyclical of Pope Paul VI, Humanae Vitae, which rejected all methods of artificial contraception. In this contribution, the author attempts to look at the problems of the culture of life in European space through the lens of several ethical and philosophical thoughts. This contribution, therefore, seeks to reflect both upon the rejection of Humanae vitae by modern Western society, as well as consider the propositions of future steps that will help stabilize European society, including the concepts of economics, family, and values according to the said encyclical.